2008
DOI: 10.1007/s10350-008-9371-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Functional Outcome of Laparoscopic Sacrocolporectopexy for Combined Vaginal and Rectal Prolapse

Abstract: The described laparoscopic procedure of mesh sacrocolpopexy with rectopexy was safe and feasible and conferred good symptomatic improvement in pelvic floor dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In a study on the feasibility and functional outcome of laparoscopic sacrocolpopexy in 10 patients with combined vaginal and rectal prolapse, Sagar et al found lower postoperative pelvic floor distress inventory scores [19]. However, it should be noted that these authors performed concomitant perineorrhaphy.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a study on the feasibility and functional outcome of laparoscopic sacrocolpopexy in 10 patients with combined vaginal and rectal prolapse, Sagar et al found lower postoperative pelvic floor distress inventory scores [19]. However, it should be noted that these authors performed concomitant perineorrhaphy.…”
Section: Discussionmentioning
confidence: 94%
“…This adverse outcome on anorectal function can be explained by the technique of laparoscopic sacrocolpoperineopexy. Indeed, in contrast to previous studies [19,20] using posterior mesh fixation to the posterior vaginal wall or to the uterine isthmus, we fixed the posterior mesh deeply into the levator ani fascia on both sides of the rectum. Thus, the rectal compliance and the anorectal angulation could possibly be altered, resulting in an increased risk of obstructed defecation.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional surgeries include transvaginal, transanal, and transperineal surgeries. It is reported that transabdominal rectal fixation or rectal suspension is targeted to severe pelvic floor relaxation complicated with pelvic organ prolapse; such surgery is not aimed at rectocele but helps treat rectocele [18]. However, such surgery has shortcomings.…”
Section: Hemicolectomymentioning
confidence: 98%
“…When ERP is associated with cystocele and/or hysterocele, they should be repaired simultaneously. Even though simultaneous open abdominal repair or the combination of laparoscopic and perineal approaches to the coexisting POP and ERP has been reported to have been employed [11][12][13] , si- Figure 1. a.…”
Section: Introductionmentioning
confidence: 99%
“…a. The schema of the POP-Q score (figure modified from that of a previous study (13). Positions are expressed as centimeters above the hymen (negative number) or centimeters below the hymen (positive number) with the plane of the hymen being defined as zero.…”
Section: Introductionmentioning
confidence: 99%